Thrombospondin-4 Is a Soluble Dermal Inflammatory Signal That Selectively Promotes Fibroblast Migration and Keratinocyte Proliferation for Skin Regeneration and Wound Healing - Klaas, Mariliis; Mäemets-Allas, Kristina; Heinmäe, Elizabeth; Lagus, Heli; Cárdenas-León, Claudia Griselda; Arak, Terje; Eller, Mart; Kingo, Külli; Kankuri, Esko; Jaks, Viljar (Frontiers in Cell and Developmental Biology, 2021)
Thrombospondin-4 (THBS4) is a non-structural extracellular matrix molecule associated with tissue regeneration and a variety of pathological processes characterized by increased cell proliferation and migration. However, the mechanisms of how THBS4 regulates cell behaviour as well as the pathways contributing to its effects have remained largely unexplored. In the present study we investigated the role of THBS4 in skin regeneration both in vitro and in vivo. We found that THBS4 expression was upregulated in the dermal compartment of healing skin wounds in humans as well as in mice. Application of recombinant THBS4 protein promoted cutaneous wound healing in mice and selectively stimulated migration of primary fibroblasts as well as proliferation of keratinocytes in vitro. By using a combined proteotranscriptomic pathway analysis approach we discovered that β-catenin acted as a hub for THBS4-dependent cell signaling and likely plays a key role in promoting its downstream effects. Our results suggest that THBS4 is an important contributor to wound healing and its incorporation into novel wound healing therapies may be a promising strategy for treatment of cutaneous wounds.